2021
DOI: 10.1016/j.ebr.2021.100465
|View full text |Cite
|
Sign up to set email alerts
|

Acquired visual agnosia as an uncommon presentation of epileptic encephalopathy in a 6-year-old boy with CSWS

Abstract: Highlights Acquired visual agnosia is an underrecognized and rare manifestation of CSWS. Highly specific spared and affected areas of visual performance may be seen. Methylprednisolone was found most effective to treat cognitive symptoms. Recovery on EEG (SWI) and neuropsychological results showed partial synchronicity. SWI is likely not the only neurophysiological marker of epileptic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…It should not be forgotten that any Among the neuropsychiatric clinical features in atypical ESES, ADHD-like symptoms are prominent and seem to be related positively to SWI [40]. Acquired visual agnosia may be found in CSWS, as suggested in the case reported by Van Iterson et al: a male aged almost 7 years presenting CSWS, prevailing in the left posterior regions, who lost the skill of recognizing familiar faces and naming pictures [41]. Kuki et al reported acquired Kanji (morphogram) dysgraphia associated with visual processing impairment in two children with CSWS prevailing in the occipito-temporal region, in which functional neuroimaging showed a dysfunction located in the left posterior temporal lobe [42].…”
Section: Eegs and Clinics Of Typical And Atypical Esesmentioning
confidence: 86%
“…It should not be forgotten that any Among the neuropsychiatric clinical features in atypical ESES, ADHD-like symptoms are prominent and seem to be related positively to SWI [40]. Acquired visual agnosia may be found in CSWS, as suggested in the case reported by Van Iterson et al: a male aged almost 7 years presenting CSWS, prevailing in the left posterior regions, who lost the skill of recognizing familiar faces and naming pictures [41]. Kuki et al reported acquired Kanji (morphogram) dysgraphia associated with visual processing impairment in two children with CSWS prevailing in the occipito-temporal region, in which functional neuroimaging showed a dysfunction located in the left posterior temporal lobe [42].…”
Section: Eegs and Clinics Of Typical And Atypical Esesmentioning
confidence: 86%
“…Agnosia is an inability to identify and recognize objects, sounds or persons using either one or more of their senses even though the senses have a normal function (Kumar, 2023). Visual agnosia has been described as a group of neurological disorders in which the affected individual cannot recognize some or all aspects of an object by sight but by other means such as sound or touch (Barton, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The deficit in vision is unexplainable by language problems, memory, attention, or unfamiliarity with the stimuli in question. It is an impairment of the ability to recognize using vision despite an otherwise normal visual acuity, visual field, color vision, language memory and brightness discrimination (Kumar, 2023). One of the earliest experiments was observed by Munk, who described some dogs who avoided some objects in the environment although they could not recognize it.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations